Influence of peers' actual appraisals on moral self-representations of Chinese adolescents - Yue, Caizhen; Long, Yihong; Ou, Kaihua; Dong, Xiaofang; Cao, Fasheng (Frontiers in Psychology, 2022)
Adolescence is a vital period of developing a moral self. As individuals enter adolescence, peers become increasingly important to them. This study aimed to explore the influence of peers' actual appraisals on moral self-representations. Based on Looking Glass Self Hypothesis, peers' reflected appraisals usually have a mediating effect on peers' actual appraisals and self-appraisals. This study used the Chinese Moral Trait Words Rating Scale to investigate 160 dyads of Chinese adolescents (12–14 years old). The participants filled in the Self-Appraisals Questionnaire, Peers' Reflected Appraisals Questionnaire, and Peers' Actual Appraisals Questionnaire, respectively. The results showed that: (a) peers' actual appraisals indirectly affected self-appraisals through peers' reflected appraisals in the process of forming the moral self of early Chinese adolescents; (b) Chinese adolescents had a certain accuracy in peers' actual appraisals, but often underestimated their peers' actual appraisals of them. This study was conducive to understanding the influence of peers on forming adolescents' moral self in the context of collectivistic culture.